ANALYSIS OF THE CHARACTERISTICS OF CYCLIC SYNCHRONIZATION SYSTEMS WITH THE USE OF THE PTP PROTOCOL (IEEE1588v2) - Kolyadenko, Yu. Yu.; Shostko, I. S.; Ageev, D. V. (Radio Electronics, Computer Science, Control, 2019)
Context. The article presents the results of the analysis of synchronization characteristics in the networks of the new generation using the PTP protocol. The object of the research is the synchronization process in the networks of the new generation using the PTP protocol (IEEE1588v2). The purpose of this work is to analyze the characteristics of synchronization in the networks of the new generation using the PTP protocol. Method. The main causes of frame alignment failures are out of synchronism. This leads to a change in the cycle duration, since one or several clock intervals will appear in the cycle, or the clock symbols will become distorted as a result of interference. In this case, an important characteristic of the synchronization system is the average retention time. A set of synchronization characteristics in the networks of the new generation using the PTP protocol is proposed: the average retention time of frame alignment; average time to fill the drive to get out of sync; the average time of filling the drive at the entrance to synchronism and the average time of searching for a sync group. Results. The analysis of the proposed synchronization characteristics in the networks of the new generation using the PTP protocol has been carried out. A study was made of the dependence of the average cycle hold time for a non-adaptive receiver of a cyclic clock signal on the probability of distortion of a single symbol in the group path. A study was conducted of the dependence of the average filling time of a drive for sync matching from the capacity of the drive for sync matching. A study was made of the dependence of the average drive fill time on an entry into synchronism for a non-adaptive receiver of a cyclic sync signal on the probability of distortion of a single symbol in a group path. A study was made of the dependence of the average search time of a sync group for a non-adaptive receiver of a cyclic sync signal on the length of a code combination of a sync group. A study was made of the dependence of the average sync group search time for a non-adaptive receiver of a cyclic sync signal on the number of symbols between two sync signals. Conclusions. Conducted studies of the characteristics of synchronization allow us to make recommendations on the application of the PTP protocol in specific practical situations. Prospects for further research may lie in the development of sync code words.